Topics in the Theory of Chemical and Physical Systems Proceedings of the 10th European Workshop on Quantum Systems in Chemistry and Physics held at Carthage, Tunisia, in September 2005 - Maruani, Jean; Lahmar, Souad; Delgado-Barrio, Gerardo (Progress in Theoretical Chemistry and Physics, 2007)
Topics in the Theory of Chemical and Physical Systems is a collection of 14 selected papers from the scientific presentations made at the 10th European Workshop on Quantum Systems in Chemistry and Physics held at Carthage, Tunisia, in September 2005. This book encompasses a spectrum of topics in which emphasis is placed on theoretical methods in the study of chemical and physical properties of various systems: Advanced Methodologies Interactions and Clusters Excited States and Condensed Matter This volume is an invaluable resource for all academics and researchers interested in theoretical, quantum or computational chemistry, physical chemistry and chemical physics, particularly molecular structure and spectroscopy, interactions and complexes. It presents a selection of some of the most advanced methodologies, results and insights in these various areas.